THE INTENSITY OF BIOFILM FORMATION ON TITANIUM AND ZIRCONIA ABUTMENTS DURING TREATMENT WITH IMPLANT-SUPPORTED PROSTHESES - S.-R. R. Ghot; M.M. Ugrin; O.M. Fal; A.Ya. Baryliak; M.A. Panas (Український стоматологічний альманах)
Bacterial adhesion is directly related to the character of the surface structure. It is also known that the adhesion intensity of bacteria varies depending on the material but there are not many studies which compare the intensity of biofilm formation, its bacteria and the impact on soft tissues. The microflora around dental implants appears to be similar to that which found around natural teeth and, thus, microbial pathogens associated with periodontitis may also contribute to implant failures. The surface of supraosseous implant elements is essential for the dental plaque formation and studies of its properties would prevent the process of periimplantitis. For the experiment three types of titanium disks (mechanically polished, sandblasted and acid-etched and Titanium Nitride surface) and zirconium oxide discs were used. We studied the bacterial colony formation on these samples. Experiment showed different adhesion properties of the bacteria depending on the surface character of the experimental material.